GRAMMATICAL FEATURES OF THE ENGLISH LANGUAGE: SYNTAX AND MORPHOLOGY (Web of Technology: Multidimensional Research Journal, 2024)
This article is devoted to the grammatical features of the English language with an emphasis on syntax and morphology. It examines the main aspects that influence the structure of the English language, such as word order, the use of parts of speech, and the rules for the formation of word forms. Particular attention is paid to the differences between syntactic constructions and morphological categories, as well as their role in the formation of meanings. The article aims to understand how grammatical features affect communication and offers practical examples to illustrate key concepts. The study will be useful both for students of English and for linguists interested in its grammatical structure.